Asian Flu Pandemic in Indonesia, 1957: Government and Public Response - Fakhriansyah, Muhammad; Kurniawati, Kurniawati (Indonesian Historical Studies, 2024)
This study aims to analyze the 1957 Asian Flu Pandemic in Indonesia, focusing on the government and public response. The 1957 Asian Flu Pandemic was the second pandemic in the world after the 1918 Spanish Flu Pandemic. The pandemic was caused by the H2N2 influenza virus and originated in China. From China, the virus spread to Hong Kong, Singapore, and the world, including Indonesia. The Asian flu was the first pandemic faced by the post-colonial government of the Republic of Indonesia. The pandemic occurred in Indonesia between May and August, with the number of sufferers reaching 202,469 people (according to the government). Using historical methods, this study shows that the existence of the Asian flu indirectly tested the government's work and readiness in dealing with a global pandemic. The Asian flu pandemic struck when the Indonesian government faced difficult problems after the War of Independence (1945-1949). This situation made it difficult for the government to act. Therefore, the policy of responding to the Asian flu seemed very careful and even slow. In addition, the lack of health sector services and infrastructure in various regions also interfered with handling the pandemic. This situation also caused poor coordination between the central and regional governments. As a result, the public became confused. People end up acting without direction, such as trying traditional medicine, spreading hoax news, violating quarantine rules, committing vaccination fraud, panic buying, and even performing various mystical rituals.